Nanobiodiversity and Biomimetic Adhesives Development: From Nature to Production and Application - Espinoza-Ramirez, Angelo (2019)
Advances in science and technology, especially in bioprospecting and biomimetics, have provided solutions to everyday problems over time. Through bioengineering, research and the discovery of the mechanisms present in nature for the production and functionality of adhesives, different materials and substances capable of imitating the role of their analogs in nature have been developed, which generates positive consequences in the area of the medical, textile, wood industry, among others. In this review, we present some researches and discoveries that have been made, which focus on the way in which adhesives produced by organisms found in nature are made, such as: marine organisms, plants, land organisms, insects, among others. In addition, different types of adhesives that exist and how they can be produced synthetically to be oriented to several industrial applications are mentioned, too.